A New Classification of Anterior Choroidal Artery Aneurysms and Its Clinical Application - Duan, Yu; Qin, Xuanfeng; An, Qinqzhu; Liu, Yikui; Li, Jian; Chen, Gong (Frontiers in Aging Neuroscience, 2021)
Background and purpose: The aim was to compare different subtypes of anterior choroidal artery (AChoA) aneurysms based on the new classification and to analyze the risk factors by individual endovascular treatment (EVT). Methods: In the new classification, AChoA-aneurysms were classified into independent type (Ⅰ type) and dependent type (Ⅱ type) based on the relationship between AChoA and aneurysms, Ⅱ type aneurysms had three subtypes-Ⅱa (neck), Ⅱb (body) and Ⅱc (direct). From 2015 to 2019, Fifty-two cases with AChoA aneurysm were analyzed retrospectively. 13 aneurysms (25.0%) were Ⅰ type; 24 aneurysms (46.2%) were Ⅱa, 15 aneurysms (28.8%) were Ⅱb and no Ⅱc type and 28 cases had subarachnoid hemorrhage. According to the preoperative EVT plan for different subtypes: Ⅰ type would achieve Raymond-Roy occlusion class 1 (RROC 1) as much as possible; for keeping AChoA, it is best to preserve the Ⅱa type aneurysms’ neck (RROC 2) and RROC 3 is enough for Ⅱb type. Results: Ten asymptomatic cases with minimal aneurysm were given conservative treatment; 42 cases were treated by individualized EVT: 26 aneurysms by simple coil, 6 by balloon-assisted coiling, 7 by stenting assisted coiling and 3 by Flow Diverter. different subtypes had different RROC (Z=14.026, P=0.001). Ⅱb type aneurysms (2=7.54, P=0.023) was the one of potential factors for AChoA temporarily or permanently injured during operation. Two (Ⅱa=1, Ⅱb =1) developed contralateral hemiparesis. Conclusions: The new classification diagram can clearly show the feature of all kinds of AChoA aneurysms and make EVT plan more explicitly. The Ⅱ type (specially Ⅱb) was one of potential risk factors for AChoA injured.